(untitled) (CAHIERS MAGELLANES-NS, 2024)
In addition to hyperlipemia and hyperglycemia, type II diabetes is characterized by decreased insulin secretion, obesity, and a significant risk to one's health. The purpose of this study was to determine whether pranayamas and yoga poses have any bearing on particular metrics. Two groups comprising one hundred individuals (aged 40 to 55) with type-II D.M. without complications were formed. those in group B practiced yoga in addition to conventional medicine, while those in group A received conventional medicine alone. The trial lasted for ninety days. HbA1C, lipid profile, and blood glucose baseline measurements were obtained during enrollment and again after 90 days of research. Results revealed that group B patients had a significant improvement in all biochemical indicators, with the exception of TG, whereas group A patients demonstrated